RELATIONAL GEOGRAPHIES: THE PARTY AT THE FATIMA’S SANCTUARY IN FORTALEZA - CE - Cavalcante, Tiago Vieira (2012)
The aim of this paper is to demonstrate what the geographical sense of the party dynamic in the relational context. For this, we went to Fatima Sanctuary in Fortaleza - CE to analyze the movements which builds the festive sense that the sanctuary has, as well the legitimacy and posterity that the party offers to the representations linked to it. The relational geography enters, in that sense, as a daily practice responsible for preparing the fleeting moment that is the party and their spatial and temporal aftermaths which accompany the sense of Fatima Sanctuary permanently.